THE ROLE OF MOTIVATION ON ORGANIZATIONAL COMMITMENT OF MANAGEMENT PROGRAM S1 LECTURERS AT PRIVATE UNIVERSITIES IN THE CITY OF BANDUNG - Rahayu, Muji (Dinasti International Journal of Management Science, 2020)
This study wants to examine whether motivation affects the organizational commitment of lecturers. The population is a Lecturer in Management Study Program of a private university in the city of Bandung. The total sample of 50 Management Study Program Lecturers is taken randomly. Data was collected by means of a survey using a questionnaire. Furthermore, the data is processed using a simple linear regression method to find out and analyze the effect of motivation on the organizational commitment of lecturers. It is hoped that the results of this research can increase the motivation of lecturers, which in turn can increase the organizational commitment of lecturers. The results showed that motivation has a positive and significant influence on organizational commitment of Management Study Program lecturers in Bandung.